DERADIKALISASI PAHAM AGAMA MELALUI ORGANISASI EKSTRA KAMPUS DI UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG - Guntur Cahaya Kesuma; Amirudin Amirudin; Subandi Subandi; Dedi Lazwardi; Istihana Istihana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
The purpose of this paper is to describe holistically the role of extra-campus organizations, especially those at the Radin Intan Islamic State University in Lampung in suppressing radical understanding and fostering moderate Islamic values ​​in the academic environment. This paper is the result of research using a phenomenological approach, aimed at describing the situation or phenomenon that occurs. The method used is a qualitative method in the form of qualitative descriptive analysis. The conclusions of this research are as follows: (1) Understanding the concept of moderate Islamic values ​​that are non-violent (Rahmatan lil 'alamin) in tackling radical understanding at Raden Intan State Islamic University in Lampung using Tawasut, Tasamuh, Tawazun and I'tidal Amar Ma'ruf Nahi Munkar (2) Extra-campus student organizations have a very important role in counteracting radical understanding by socializing and implementing extra-campus student organizations activities that are based on moderate Islamic understanding and implementing the values ​​of Pancasila as the basis of state philosophy. 3) The impact of optimizing the implementation of moderate Islamic values ​​in the activities of extra-campus organizations is very high, this is obtained from the results of the questionnaire students' perceptions about the actualization of moderate Islam with a value of 91%. Tolerance is a characteristic of the Indonesian nation that must be developed in order to strengthen the value of fellow human beings and as an antidote to radical understanding.